Protective effect of 6-paradol in acetic acid-induced ulcerative colitis in rats - Misbahuddin Rafeeq; Hussam Aly Sayed Murad; Hossam Mohammed Abdallah; Ali M. El-Halawany (BMC, 2021)
Abstract Background Ulcerative colitis is a gut inflammatory disorder due to altered immune response to gut microbiome, with interplay of environmental and genetic factors. TNF-α activates inflammatory response through a cascade of immune responses, augmenting pro-inflammatory mediators and proteases, activating chemotaxis, and infiltration of inflammatory cells, leading to ulceration and haemorrhage through cytotoxic reactive oxygen species. 6-Paradol, a dietary component in several plants belonging to the Zingiberaceae family, has shown anti-inflammatory and antioxidant activities. Current study evaluates the effect of 6-paradol in amelioration of ulcerative colitis in rats for the first time. Methods 6-Paradol (95% purity) was obtained from seeds of Aframomum melegueta. Rats were divided randomly into six groups (n = 8). Group one was administered normal saline; group two was treated with the vehicle only; group three, sulfasalazine 500 mg/kg; and groups four, five, and six, were given 6-paradol (50, 100, 200, respectively) mg/kg orally through gastric gavage for 7 days. Colitis was induced on 4th day by intrarectal administration of 2 ml acetic acid (3%), approximately 3 cm from anal verge. On 8th day, rats were sacrificed, and distal one-third of the colon extending proximally up to 4 cm from anal orifice was taken for biochemical and gross examination. Two centimetres of injured mucosal portion was taken for histopathological investigations. SPSS (ver.26) was used for statistical analysis. Results Colonic and serum glutathione (GSH) levels decreased, while colonic and serum malondialdehyde (MDA), colonic myeloperoxidase (MPO) activity, serum interleukin-6 (IL-6), serum tumour necrosis factor-α (TNF-α) levels, and colon weight to length ratio were increased significantly in the colitis untreated group compared to normal control. Treatment with 6-paradol considerably improved all these parameters, especially at a dose of 200 mg/kg (p < 0.001), revealing non-significant differences with sulfasalazine 500 mg/kg and normal control (p = 0.998). Sulfasalazine and 6-paradol in a dose dependent manner also markedly reversed mucosal oedema, atrophy and inflammation, cryptic damage, haemorrhage, and ulceration. There were non-significant differences between low and medium doses and between medium and high doses of 6-paradol for IL-6 and serum MDA levels. Conclusion 6-Paradol demonstrated protection against acetic acid-induced ulcerative colitis, probably by anti-inflammatory and antioxidant actions.